EUPHEMISM FOUND IN CELEBRITY NEWS PUBLISHED IN PEOPLE.COM WEBSITE - Deka Novianti; Hermawati Syarif; Leni Marlina (English Language and Literature, 2018)
Euphemism is one of language phenomena that exists in society in order to keep the relationship in good harmony. This research aims to describe forms and functions of euphemism that are found in Celebrity News published in people.com website. This research is descriptive qualitative based on phenomena of euphemism in written language. Data of this research are words, phrases and sentences that contain euphemistic expression found in Celebrity News during February 2017.The result of the research shows that there are four forms and four functions of euphemism. The form of euphemism that is mostly found is semantic change, especially metaphorical transfer. The researcher also found various functions of euphemism. The function of euphemism that is mostly found is avoiding taboo.